When are ghettos bad? Lessons from immigrant segregation in the United States - Cutler, David M. 1965-; Glaeser, Edward L. 1967-; Vigdor, Jacob L. (National Bureau of Economic Research, 2007)
Recent literature on the relationship between ethnic or racial segregation and outcomes has failed to produce a consensus view of the role of ghettos; some studies suggest that residence in an enclave is beneficial, some reach the opposite conclusion, and still others imply that any relationship is small. This paper presents new evidence on this relationship using data on first-generation immigrants in the United States. Using average group characteristics as instruments for segregation, controlling for individual characteristics and both metropolitan area and country-of-origin fixed effects, we estimate impacts of residential concentration that vary with group human capital levels. Residential concentration can be beneficial, but primarily for more educated groups. The mean impact of residential concentration varies across measures, which may illuminate some of the causal mechanisms relating segregation to outcomes.